Evaluation of Phase Feeding and Complete Diet Blending at Different Standardized Ileal Digestible Lysine Levels on Growing-Finishing Pigs’ Growth Performance, Carcass Characteristics, and Diet Economics - Ron Aldwin S. Navales; Mike D. Tokach; Dwayne A. Krogstad; Joel M. DeRouchey; Jordan T. Gebhardt; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,160 mixed-gender pigs (PIC 337 × 1050; initially 54.8 ± 9.4 lb) were used in the 120-d study to compare feeding strategies (phase feeding vs. complete diet blending) at different SID Lys levels (90 vs. 100% of requirement estimates) on finishing pig growth performance, carcass characteristics, and economics. Pens of pigs were randomly assigned to 1 of 4 treatments following a completely randomized block design with barn and initial body weight as blocking factors. The treatments included two feeding programs, a 5-phase feeding strategy at either 90% (Phase-90) or 100% of SID Lys requirement estimates (Phase-100); or two programs with complete diet blending, with pre-defined mixing proportions of a low and high SID Lys diet to meet 90 (Blend-90) or 100% (Blend-100) of the SID Lys curve requirement estimates for 50- to 280-lb pigs. Pigs in the phase-feeding strategies were fed on a feed budget with 47, 144, 147, 138, and 136 lb of feed per pig for phases 1 to 5, respectively. Body weights at any period of the trial and overall ADG (d 0 to 120) were not affected by the feeding strategy nor by diet SID Lys levels. In contrast, the overall ADFI of pigs fed by diet blending was lower than the ADFI of those fed by phase feeding (P= 0.002), resulting in improved F/G (P<0.001). The SID Lys levels did not influence overall ADFI or F/G. Hot carcass weight, carcass yield, lean percentage, fat depth, and loin depth were not affected by the feeding program. Despite the lower overall ADFI of pigs fed by diet blending, the feeding strategy resulted in no significant differences in economic criteria except for feed cost per lb of gain at the high price scenario (P= 0.049). With low diet cost, the 90% SID Lys level resulted in lower feed cost per pig and feed cost per lb of gain than 100% SID Lys, but this was not reflected in income over feed cost (IOFC). In conclusion, diet blending at either 90 or 100% of the SID Lys requirement estimate improved F/G by reducing ADFI without impacting ADG or carcass characteristics. At current prices used in this study, feeding strategies at either 90 or 100% SID Lys did not significantly affect IOFC, but feeding 90% of the SID Lys recommendation reduced the feed cost.
Keywords: diet blending; finishing pigs; phase feeding